Managerial Knowledge and Values in Saudi Healthcare: Sustainability Reporting and Commitment - Ahmed ElRabbat, Samar; Benarous, Djamel; Hassan ElAwad, Islah; El Hamdi, Rabeb; Ahmad Barakat, Shaima; Nasser Alsharif, Bashayr (European Journal of Sustainable Development, 2025)
Secondary processes in hospitals are causing a major part of hospitals’ carbon footprint. At the same The purpose of this paper is to examine the effect of managerial knowledge and organizational values on the implementation of sustainability reporting practices in the healthcare sector in Saudi Arabia. It also focuses on the mediating effect of organizational commitment in this relationship. Through a quantitative analysis using a questionnaire distributed to a sample of 264 administrators at organizational levels in the health sector in the Kingdom of Saudi Arabia, the research identifies key factors that drive the implementation of sustainability reporting and highlights the importance of aligning managerial competencies and organizational values with sustainability goals. The results of the study show that raising the level of knowledge of managers and encouraging the right organizational values are important to enhance commitment, which in turn, improve the effectiveness of sustainability reporting. For healthcare organizations that want to integrate sustainability into their business processes, this paper offers practical implications and provides valuable insights for healthcare organizations aiming to integrate sustainability into their operational frameworks. Keywords: Sustainability Reports, Managerial Knowledge, Organizational Values, Organizational Commitment, Environmental Sustainability, Corporate Social Responsibility